The prosodic marking of rhetorical questions in Standard Chinese. (November 2022) - Zahner-Ritter, Katharina; Chen, Yiya; Dehé, Nicole; Braun, Bettina
Highlights: Prosody differentiates information-seeking and rhetorical questions in Standard Chinese. Prosodic differences between illocution types occur in both polar and wh -questions. Rhetorical questions are lower, longer, and realized more often with glottalized voice. Prosodic cues to rhetorical questions are modified in tandem. Cross-linguistic findings may be explained by assertive force, focus, or speaker attitude. Abstract: The present study investigates the prosody of information-seeking (ISQs) and rhetorical questions (RQs) in Standard Chinese, in polar and wh -questions. Like in other languages, ISQs and RQs in Standard Chinese can have the same surface structure, allowing for a direct prosodic comparison between illocution types (ISQ vs RQ). Since Standard Chinese has lexical tone, the use of f0 as a cue to illocution type may be restricted. We investigate the prosodic differences between ISQs and RQs as well as the interplay of prosodic cues to RQs. In terms of f0, results showed that RQs were lower in f0, with the f0 range on the first word being expanded followed by f0 compression. RQs were further longer in duration and more often realized with non-modal voice quality (glottalized voice) as compared to ISQs. These prosodic cues were largely manipulated in tandem (illocutionary pairs with larger durational differences also showed larger differences in mean f0 ; voice quality, in turn, seemed to be an additional cue). We suggest three possible explanations (assertive force, focus, speaker attitude) that unite the present findings on RQs in Standard Chinese with the findings on RQs in other, non-tonal languages.